Nanoencapsulation Of Thiolated Sodium Alginate: Synthesis, Drug Release And Cellular Uptake Studies - Chiu, Hocking (2018)
Oral drug delivery has becoming the most preferred route of administration for chemotherapeutic drugs, however its application is limited due to lack of drug targeting specificity to the localised cancerous cells but not to the normal cells. Polymeric nanoparticulate drug delivery is a potential solution to deliver hydrophobic drugs specifically to colon, thus causing less side effects.